Potensi Limbah Padat sebagai Benang Gintir Berbasis Sistem Interlacing - Nisa Fardani; Achmad Haldani Destiarmand; Andar Bagus Sriwarno (Journal of Visual Art and Design, 2015)
Sistem pengelolaan sampah di tempat pembuangan sampah menjadi masalah lingkungan yang besar seiring dengan pertumbuhan industri pulp dan kertas di Indonesia. Konversi limbah padat menjadi bahan bakar pelengkap untuk industri kertas juga tidak memberikan hasil yang signifikan untuk memecahkan masalah pencemaran udara pada saat karbon aktif dibebaskan dari proses pembakaran. Masalah ini secara khusus menuntut sistem pengelolaan sampah yang maju dan efektif secara terus-menerus. Baru-baru ini, optimasi pemanfaatan serat-limbah menjadi alternatif khusus untuk mengurangi tumpukan sampah di tempat pembuangan sampah. Namun, tidak semua dapat didaur ulang. Karakteristik limbah padat berserat dari industri kertas tisu cenderung menurun gramaturnya, sehingga sangat disayangkan pemanfaatannya akan berkurang bahkan setelah proses daur ulang. Di sisi lain, struktur kimianya yang telah rusak selama proses produksi tampaknya menjadi semangat baru bagi industri tekstil di masa depan dalam mengembangkan teknologi daur ulang limbah padat berserat, yang menghasilkan benang tekstil generasi baru. Fokus dalam penelitian ini ditekankan pada penemuan tas yang terbuat dari bahan serat-limbah menggunakan metode eksperimental. Identifikasi karakteristik serat-sampah berbasis padat dikembangkan melalui teknik eksplorasi multi-ply yarns berdasarkan sistem interlace. Hubungan antara penciptaan produk dan forecasting  tren pada tahun 2013 akan menjadi analisis berikutnya sebagai salah satu cara untuk memecahkan masalah sampah.Kata Kunci: limbah; multi-ply yarns; sistem interlacing.The Potential of Solid Waste as Multiply Yarn Based on Interlacing SystemsSolid-waste disposal in landfills is becoming a massive environmental problem as a result of the growth of the pulp and paper industry in Indonesia. The conversion of solid waste to complementary fuel for the paper industry is also not giving any significant results to solve air contamination, as active carbon is released into the atmosphere by the burning process. This particular problem demands an advanced and effective continuous waste management system. Recently, optimized waste-fiber utilization has come forward as a promising alternative to reduce the waste pile in landfills. However, not all of it can be recycled. Fibered solid waste from the tissue-paper industry tends to decrease its grammage, which unfortunately will eventually reduce its utilization after recycling. On the other hand, its chemical structure, which has already been damaged during the production process, appears to be giving inspiration for a future textile industry based on the development of fibered solid-waste recycling technology, resulting in a new generation of textile yarns. In this research, the focus is on the invention of a handbag made from fiber-waste material using experimental methods. Solid-based fiber waste characteristics identification was developed through a multi-ply yarn exploration technique based on an interlacing system. The relationship between product creation and the trend forecasting for 2013 will be our next goal as one way of solving Indonesia's waste problem.Keywords: interlacing system; multi-ply yarns; waste.